2010
DOI: 10.1007/s10126-010-9319-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Carbohydrate Fraction of the Temporary Adhesive Secreted by the Tube Feet of the Sea Star Asterias rubens

Abstract: In sea stars, adhesion takes place at the level of a multitude of small appendages, the tube feet. It involves the secretion of an adhesive material which, after tube foot detachment, remains on the substratum as a footprint. It was previously reported that the two main organic components of this material are proteins and carbohydrates. The carbohydrate moiety of the adhesive secretion of Asterias rubens was investigated using a set of 16 lectins which were used on sections through tube feet, on footprints, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
94
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(98 citation statements)
references
References 46 publications
4
94
0
Order By: Relevance
“…In previous studies, the disruption of footprints from the substratum by trypsin treatment demonstrated the crucial role of proteins for adhesion and cohesion (5,18). In the species Asterias rubens, proteins are the main organic components of the adhesive material (20% of the footprint dry weight compared with 8% for carbohydrates and 6% for lipids) (14,16). Recently, we solubilized the majority of these proteins by using denaturing and reducing conditions (14).…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…In previous studies, the disruption of footprints from the substratum by trypsin treatment demonstrated the crucial role of proteins for adhesion and cohesion (5,18). In the species Asterias rubens, proteins are the main organic components of the adhesive material (20% of the footprint dry weight compared with 8% for carbohydrates and 6% for lipids) (14,16). Recently, we solubilized the majority of these proteins by using denaturing and reducing conditions (14).…”
mentioning
confidence: 97%
“…Several unique adhesive proteins have been characterized and assigned specific bulk or surface functions. By comparison, temporary adhesives have been studied to a lesser extent, and, although the presence of specific proteins has been highlighted in some organisms, none has been fully characterized so far (10,13,14).…”
mentioning
confidence: 99%
See 3 more Smart Citations